Price Points and Price Rigidity - Daniel Levy; Dongwon Lee; Haipeng (Allan) Chen; Robert J. Kauffman; Mark Bergen (Review of Economics and Statistics, 2011)
We study the link between price points and price rigidity using two data sets: weekly scanner data and Internet data. We find that “9” is the most frequent ending for the penny, dime, dollar, and ten-dollar digits; the most common price changes are those that keep the price endings at “9”; 9-ending prices are less likely to change than non-9-ending prices; and the average size of price change is larger for 9-ending than non-9-ending prices. We conclude that 9-ending contributes to price rigidity from penny to dollar digits and across a wide range of product categories, retail formats, and retailers.
Keywords: E31; L16; D80; M21; M30; 330; Price Point; 9-Ending Price; Price Rigidity